2008
DOI: 10.1128/ec.00146-08
|View full text |Cite
|
Sign up to set email alerts
|

PKC1 Is Essential for Protection against both Oxidative and Nitrosative Stresses, Cell Integrity, and Normal Manifestation of Virulence Factors in the Pathogenic Fungus Cryptococcus neoformans

Abstract: Cell wall integrity is crucial for fungal growth, survival, and pathogenesis. Responses to environmental stresses are mediated by the highly conserved Pkc1 protein and its downstream components. In this study, we demonstrate that both oxidative and nitrosative stresses activate the PKC1 cell integrity pathway in wild-type cells, as measured by phosphorylation of Mpk1, the terminal protein in the PKC1 phosphorylation cascade. Furthermore, deletion of PKC1 shows that this gene is essential for defense against bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(162 citation statements)
references
References 51 publications
6
156
0
Order By: Relevance
“…In the absence of calcineurin, Mpk1 is able to partially protect cells from caspofungin-induced cell wall stress (285). Further studies have also shown that pkc1 mutants exhibit osmotic instability, alterations in capsule and melanin production, as well as sensitivity to temperature and cell wall-inhibiting agents (202).…”
Section: Cryptococcus Neoformans Drug Resistance: the Echinocandinsmentioning
confidence: 97%
“…In the absence of calcineurin, Mpk1 is able to partially protect cells from caspofungin-induced cell wall stress (285). Further studies have also shown that pkc1 mutants exhibit osmotic instability, alterations in capsule and melanin production, as well as sensitivity to temperature and cell wall-inhibiting agents (202).…”
Section: Cryptococcus Neoformans Drug Resistance: the Echinocandinsmentioning
confidence: 97%
“…The importance of sphingolipids for pathogenicity has also been recognized in some parasitic pathogens, including Leishmania and Trypanosoma species, and related enzymes have been proposed as potential drug targets (36,37,45,60,67). The diacyglycerol (DAG)-protein kinase C1 (Pkc1) signaling pathway is critical for virulence factor production and pathogenicity in C. neoformans (18,19,24,25). The glycophosphatidylinositol (GPI)-anchored glycolipid is derived from inositol and is necessary for pathogenicity in Candida species (61).…”
mentioning
confidence: 99%
“…The CWI pathway is conserved across many fungi (41) and is also an important regulator of the cell wall stress response in C. neoformans (12,37,44). We therefore hypothesized that Pkc1 activity may be reduced in pkh2-02⌬ mutants compared to in the WT.…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis was performed as described previously (37). Briefly, cultures were grown overnight in YPD or YNB at 30°C with shaking and then diluted to an OD 660 of 0.2 in 50 ml of medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation